La Monterita Serrana (Poospiza baeri) en la Sierra de Velazco, La Rioja (Aves: Emberizidae) - Giannini, Maximiliano; Serra, Diego A.; Urcelay, Carlos (Nuestras Aves, 2001)
Este artículo no cuenta con un resumen.